Nurturing organizational resilience: Exploring the interplay of leadership and dynamic managerial capabilities - Głód, Wojciech; Ingram, Tomasz (Organizacja i Kierowanie, 2025)
In recent years, organizational resilience has garnered significant managerial and research attention. To achieve a better understanding of the organizational and environmental factors influencing an organization's ability to respond to external threats, we investigate the impact of managerial dynamic capabilities on organizational resilience, with benevolent leadership mediating and environmental dynamism and hostility moderating this relationship. Using data from 379 Polish companies, we empirically validate the existence of a relationship between dynamic managerial capabilities and organizational resilience. Furthermore, we find that benevolent leadership plays a moderating role in this relationship. Interestingly, neither environmental dynamism nor hostility directly affected the relationship between dynamic managerial capabilities and organizational resilience, although environmental dynamism itself had a positive influence on organizational resilience.